1991
DOI: 10.1007/bf00021241
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glutenin and phenotypic diversity of Syrian durum wheat landraces in relation to their geographical origin

Abstract: Glutenin and phenotypic diversity within Syrian landraces composed of Triticum turgidum var. durum and T. aestivum was compared and related to some geographical and climatological characteristics.Glutenin diversity was determined on the basis of the composition of the glutenin fraction in kernels using Gregorius' level of population differentiation (6T) --being a modified Nei's measure of gene diversity (H) -and the Shannon-Weaver variation index (I). These two indices were highly correlated. A total of five G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…The normalised values were used in the analysis of variance of diversity for individual characters, and hierarchical analysis of variance pooled over characters. The Shannon-Weaver diversity index has been widely used in studies of germplasm collections (e.g., TESFAYE et al 1991; VAN HINTUM and ELINGS 1991;ENGELS 1994). The interpretation is that the greater the number of variants in each phenotypic class of a given character and the more nearly equal their proportions, the greater is the diversity (PIELOU 1966).…”
Section: Methodsmentioning
confidence: 99%
“…The normalised values were used in the analysis of variance of diversity for individual characters, and hierarchical analysis of variance pooled over characters. The Shannon-Weaver diversity index has been widely used in studies of germplasm collections (e.g., TESFAYE et al 1991; VAN HINTUM and ELINGS 1991;ENGELS 1994). The interpretation is that the greater the number of variants in each phenotypic class of a given character and the more nearly equal their proportions, the greater is the diversity (PIELOU 1966).…”
Section: Methodsmentioning
confidence: 99%
“…The results from various studies have shown that the three loci coding for HMW glutenin subunits are highly polymorphic in nature and their expression is strictly under genetic control without the influence of environment. Considering these properties, allelic variation at the three loci coding for HMW glutenin subunits has been used either independently or in combination with other genetic markers to estimate the genetic variation in different wheat species (Nevo & Payne, 1987;Margiotta et al, 1988;Felsenburg et al, 1991 ;van-Hintum & Elings, 1991;Ciaffi et al_, 1993). Wheat is the most important food crop of Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…A cluster analysis is an efficient mathematical method, which makes possible to study diversity among landraces using all available data (Zeven and Schachl 1989, Jaradat 1992, Zeven and Hintum 1992. Significant variability of landraces and old cultivars can be caused by their origin, then through climate, geographical and other conditions of the regions of origin (Hintum and Elings 1991). Wang and Guo (1992) found similarity in gluten alleles in accordance with geographical origin.…”
mentioning
confidence: 99%